Code Switching Found in Daniel Mananta Network Podcast by Agnes Monica and Daniel Mananta - I G B Wahyu Nugraha Putra; Putu Devi Maharani; Ni Kadek Alit Marta Dila (Prodi Sastra Inggris Fakultas Bahasa Asing Universitas Mahasaraswati Denpasar, 2023)
This study discusses the types and reasons of code-switching occurred during conversations between Agnes Monica and Daniel Mananta on the Daniel Mananta Network Podcast. This study aims to answer research problems, namely (1) What types of code switching are used by Agnes Monica and Daniel Mananta on the Daniel Mananta Network (2) What are the reasons behind the occurrence of code switching by Agnes Monica and Daniel Mananta on the Daniel Mananta Network. This study uses a descriptive qualitative method by classifying and describing the types of code switching based on the theory from Appel and Muysken (1987) and the reasons behind the occurrence of code switching based on Hoffman's theory (1991). The result shows that 90 data were found, 6 data of tag switching, 70 data of intra-sentential switching, and 13 data of inter-sentential switching. Intra-sentential switching is the most dominant types found in data source. Meanwhile, tag switching is the least. Moreover seven reasons motivating code switching were found in Podcast Daniel Mananta Network. Where talking about particular topic is the most dominant reasons found. It's because Agnes Monica and Daniel Mananta occasionally favor using one language over another while discussing a certain subject. In a language other than his native tongue, a speaker may occasionally feel more at ease and free to express his or her emotional feelings. The character can grab the audience's attention and add interest to the narrative by using code switching.